Religious and ethnic revival in a Chinese minority: the Bai people of Southwest China - Liang, Yongjia (Routledge contemporary Asia series, 2018)
"This book is based on anthropological fieldwork among the Bai, an ethnic minority with a population of two million in Dali, southwest China. It explores the religious and ethnic revival in the last two decades against a historical background. It explains why and how religions and ethnic identity are revived in contemporary China, with the revived analytical concept of 'alterity', which suggests a world beyond here and now. The book focuses on the particular institutions and ritual technologies that seek for access to the invisible, transcendental other--both spatial and temporal. It covers a variety of topics, including pre-modern kingship, communist utopia, religious alterity, ethnic identity, religious associations, the intangible cultural heritage, and temple restorations"--